Structural and Luminescent properties of Eu-doped CaAl2O4 Nanophosphor by sol-gel method. (2017) - Freeda, M.; Suresh, G.
Abstract: Calcium Aluminate nanophosphor doped with Europium (CaAl2 O4 : Eu) was synthesized by simple sol–gel route. The obtained nanophosphor was characterized by X-ray diffraction technique (XRD). The surface morphology was determined by scanning electron microscopy (SEM). Also photoluminescence spectra (PL), characterization were done. The XRD revealed the formation of monoclinic structure and the particle size was determined by Scherrer formula. The particle size was found to be 72 nm. It was observed, that PL emission was obtained at 390 nm, 520 nm, 790 nm corresponding to blue, green and IR region of the spectrum, respectively for 360 nm excitation. Also, PL emission was obtained at 395 nm, 535 nm, 805 nm for 800 nm excitation. When comparing up-conversion luminescence with down-conversion, the up-conversion luminescence spectra were red shifted.